Right ventricular contraction patterns in healthy children using three-dimensional echocardiography - Valle, Christopher; Ujvari, Adrienn; Elia, Eleni; Lu, Minmin; Gauthier, Naomi; Hoganson, David; Marx, Gerald; Powell, Andrew J.; Ferraro, Alessandra; Lakatos, Bálint; Tősér, Zoltán; Merkely, Béla; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: The right ventricle (RV) has complex geometry and function, with motion along three separate axeslongitudinal, radial, and anteroposterior. Quantitative assessment of RV function by two-dimension echocardiography (2DE) has been limited as a consequence of this complexity, whereas newer three dimensional (3D) analysis offers the potential for more comprehensive assessment of the contributors to RV function. The aims of this study were to quantify the longitudinal, radial and anteroposterior components of global RV function using 3D echocardiography in a cohort of healthy children and to examine maturational changes in these parameters. Methods: Three-dimensional contours of the RV were generated from a cohort of healthy pediatric patients with structurally normal hearts at two centers. Traditional 2D and 3D echo characteristics were recorded. Using offline analysis of 3D datasets, RV motion was decomposed into three components, and ejection fractions (EF) were calculated (longitudinal-LEF; radial-REF; and anteroposterior-AEF). The individual decomposed EF values were indexed against the global RVEF. Strain values were calculated as well. Results: Data from 166 subjects were included in the analysis; median age was 13.5 years (range 0 to 17.4 years). Overall, AEF was greater than REF and LEF (29.2 ± 6.2% vs 25.1 ± 7.2% and 25.7 ± 6.0%, respectively; p < 0.001). This remained true when indexed to overall EF (49.8 ± 8.7% vs 43.3 ± 11.6% and 44.4 ± 10%, respectively; p < 0.001). Age-related differences were present for global RVEF, REF, and all components of RV strain. Conclusions: In healthy children, anteroposterior shortening is the dominant component of RV contraction. Evaluation of 3D parameters of the RV in children is feasible and enhances the overall understanding of RV function, which may allow improvements in recognition of dysfunction and assessment of treatment effects in the future.